Development of graphene based nanocomposites towards medical and biological applications - Mousavi S.M.; Low F.W.; Hashemi S.A.; Lai C.W.; Ghasemi Y.; Soroshnia S.; Savardashtaki A.; Babapoor A.; Pynadathu Rumjit N.; Goh S.M.; Amin N.; Tiong S.K. (Taylor and Francis Ltd., 2023)
Biocompatibility; Chemical vapor deposition; Controlled drug delivery; Nanocomposites; Quality control; Targeted drug delivery; Biological applications; Camptothecin (CPT); Chemical vapour deposition; Cytotoxic effects; Drug delivery applications; Functionalisation; Graphene nanocomposites; High specific surface area; Graphene; antiinfective agent; camptothecin; doxorubicin; firtecan; graphene; graphene oxide; nanocomposite; polymer; graphite; nanocomposite; biocompatibility; bioimaging; chemexfoliation; chemical procedures; chemical vapor deposition; cytotoxicity; diagnosis; drug delivery system; epitaxy; HCT 116 cell line; human; imaging; in vitro study; nonhuman; reduction (chemistry); regenerative medicine; Review; synthesis; tissue engineering; animal; chemistry; nanomedicine; procedures; Animals; Graphite; Humans; Nanocomposites; Nanomedicine